PRESERVATION OF ORGANIZATIONAL KNOWLEDGE THROUGH DIGITALIZATION OF PERSONNEL ARCHIVES - Vita Arieska; Tamara Adriani Salim; Muhamad Prabu Wibowo; Mad Khir Johari B. Abdullah Sani (JIPI (Jurnal Ilmu Perpustakaan dan Informasi), 2025)
Digitizing personnel records is a strategic step that not only improves administrative efficiency but also strengthens knowledge governance within organizations. This study aims to analyze the role of personnel records digitization in improving efficiency and accessibility, preventing the risk of organizational memory loss, identifying supporting factors and barriers to implementation, and examining its implications for organizational knowledge preservation. The method used is a literature review of six research articles related to personnel records digitization in various government and private institutions in Indonesia. The results show that digitization accelerates archive retrieval, increases employee productivity, and reduces the risk of damage to physical archives. Without digitization, organizations risk facing organizational memory loss, which hinders accountability and the transfer of institutional knowledge. The main supporting factors for digitalization implementation include leadership support, regulations, technological infrastructure, and human resource competencies, while barriers include budget constraints, low digital literacy, archive complexity, and the risk of data leakage. The implications of this study show that digitization is not only a technical solution but also a long-term strategy to maintain the continuity of organizational knowledge. Theoretically, these results strengthen the integration between records management and knowledge management within the framework of Records Continuum and Organizational Memory Theory. Practically, these findings provide a basis for organizations to formulate archive digitization policies that are oriented towards efficiency as well as the preservation of institutional knowledge.